The Effect of Scrambled Text on Recount Text Generic Structure of Class X SMK Negeri 1 Siantar - Imeliana Saragih; Selviana Napitupulu (Educate : Journal of Education and Learning, 2026)
This study aimed to investigate the effect of the Scrambled Text Technique on students’ ability to identify the generic structure of recount text. The research was conducted at SMK Negeri 1 Siantar, with the students of Class X TJKT 3 as the research sample. This study used a one-group pretest–posttest pre-experimental design. Although suitable for measuring changes after treatment, it is limited by internal validity threats and lacks a control group. Short instructional periods and consistent materials were applied to reduce these threats, with future research recommended to use a control group.   The instrument used in this research was a test in the form of recount text tasks that required students to identify the generic structure of the text.The data were collected through pre-test and post-test, and the results were analyzed by comparing students’ scores before and after the treatment, The findings revealed that the students’ mean score increased from 48.40 in the pre-test to 69.00 in the post-test, with a mean gain score of 21.00 after the implementation of the Scrambled Text Technique. The gain score analysis also revealed that all students experienced improvement, with no decrease in scores. Based on the findings, it can be concluded that the Scrambled Text Technique has a positive effect on students’ understanding of the generic structure of recount text. These findings provide empirical support for the use of the Scrambled Text Technique as an effective instructional approach in enhancing students’ mastery of recount text generic structure in vocational high school contexts.